Depression and Physical Frailty Have Additive Effect on the Nutritional Status and Clinical Outcome of Chinese Peritoneal Dialysis - Cheuk-Chun Szeto; Gordon Chun-Kau Chan; Jack Kit-Chung Ng; Kai-Ming Chow; Bonnie Ching-Ha Kwan; Phyllis Mei-Shan Cheng; Vickie Wai-Ki Kwong; Man-Ching Law; Chi-Bon Leung; Philip Kam-Tao Li (Karger Publishers, 2018)
Background/Aims: Frailty and depression both contribute to malnutrition and adverse clinical outcome of peritoneal dialysis (PD) patients. However, their interaction is incompletely defined. Methods: We studied 178 adult Chinese PD patients. Physical frailty was assessed by a validated in-house questionnaire; depressive symptoms was screened by the Geriatric Depression Scale; nutritional status was determined by subjective global assessment (SGA) and malnutrition inflammation score (MIS). All patients were followed for up to 24 months for survival and hospitalization analysis. Results: There were 111 patients (62.4%) physically frail, amongst those 48 (43.2%) had depressive symptoms. Only 1 patient had depressive symptoms without frailty. There was an additive effect of depressive symptoms and physical frailty on nutritional status. For the groups with no frailty, frail but no depressive symptoms, and frail with depressive symptoms, serum albumin decreased in a stepwise manner (35.8 ± 5.6, 34.9 ± 4.4, and 32.9 ± 5.3 g/L, respectively, p=0.025); overall SGA score was 5.75 ± 0.61, 5.41 ± 0.59, and 5.04 ± 0.77, respectively (p< 0.0001), and MIS was 5.12 ± 2.30, 7.13 ± 3.22, and 9.48 ± 3.97, respectively (p< 0.0001). At 24 months, patient survival was 86.6%, 71.4%, and 62.5% for patients with no frailty, frail but no depressive symptoms, and frail with depressive symptoms, respective (p=0.001). The median number of hospital stay was 8.04 (inter-quartile range [IQR] 0.91 - 19.42), 14.05 (IQR 3.57 - 37.27), and 26.62 (IQR 10.65 - 61.18) days per year of follow up, respectively (p< 0.0001). Conclusion: Physical frailty and depressive symptoms are both common in Chinese PD patients, and they have additive adverse effect on the nutritional status and clinical outcome.